Погребение номада сер.VII в. у села Дмитровка в Южном Побужье - Комар, А.В. (Інститут археології НАН України, 2006)
The paper presents the intake burial 12 of barrow 1 near Dmitrovka village on the right bank of the Yuzhny Bug river. On the basis of the analysis of the design and arrangement of silver parts of footwear straps the reconstruction of a soft boot bandage is displayed. By the rite used the burial is close to monuments of Sukhanovo type and reflects either the final stage of their development or the incorporation of individual groups of the Bulgarian population of “Sukhanovo” tradition into the Pereshchepina culture in the 3rd quarter of the VII c.